Peran Polri dalam Penegakan Hukum Terhadap Perdagangan Barang Impor Ilegal di Wilayah Hukum Polres Pelabuhan Tanjung Perak - Tio Tondy (Universitas Airlangga, 2019)
Indonesia is a country rich in natural resources. The results of natural resources owned are used to meet domestic needs and are exported overseas. Although Indonesia is rich in natural resources, there are limitations to the field of human resources. Limited human resources, including limitations in producing goods, is one of the driving factors in importing goods from abroad to enter Indonesia. Based on the Minister of Trade Regulation No. 48 of 2015 it is known that imported goods are grouped in: a. free imported goods; b. restricted import goods; and c. prohibited import goods. The limitation of imported goods is not without reason, but is in accordance with the facts found in the field that there has been an illegal trade in imported goods entering the territory of the Republic of Indonesia. Even though the Government itself has set various legal products to protect the implementation of import activities to meet the people's needs. In addition, the fact that free trade tends to result in circulating goods and or services does not necessarily guarantee the security, safety and health of consumers. The rise of illegal trade activities, led to the need for a thesis research entitled